Increased Expression of Protease Activated Receptor-2 (PAR-2) in Balloon-Injured Rat Carotid Artery - Damiano, Bruce P.; D’Andrea, Michael R.; de Garavilla, Lawrence; Cheung, Wai-man; Andrade-Gordon, Patricia (Thrombosis and Haemostasis, 1999)
Protease-induced cell signaling is mediated by specific receptors such as the emerging family of protease activated receptors (PARs). Since proteases are involved in various aspects of vascular injury, we assessed expression of PAR-2, a protease-activated receptor closely related to the thrombin receptor (PAR-1) but activated by an unknown protease, in vascular injury. Rat carotids were subjected to balloon-catheter injury and perfusion fixed at 1, 3, 7 or 14 days after injury. Sections of injured and normal carotid arteries were immunohisto-chemically labeled with a polyclonal antibody raised against the N-terminal residues 37-53 of human PAR-2. Sections were also labeled with antibodies to factor VIII-related antigen, smooth muscle actin and a proliferating cell nuclear antigen (PCNA). In normal vessels, PAR-2 labeling was diffuse and patchy in medial smooth muscle and endothelium. At one and three days after injury, before appearance of neointima, PAR-2 labeling increased in cells adjacent to damaged or necrotic smooth muscle cells. In addition, proliferating adventitial myofibroblasts labeled strongly for PAR-2. At 7 and 14 days after injury, the media and neointima of injured vessels had increased PAR-2 labeling which was most intense at the luminal edge of the neointima. Double immunohistochemical labeling confirmed the greatest expression of PAR-2 in areas with the greatest density of PCNA-positive cells. In addition, PAR-2 mRNA localization using in situ hybridization paralleled PAR-2 expression. The data suggest an upregulation of PAR-2 in response to vascular injury which is associated with medial smooth muscle damage, proliferating adventitial myofibroblasts and smooth muscle cells of the neointima, particularly those at the proliferating luminal edge of the neointima. Possible functional consequences of this receptor upregulation and its role in the response to vascular injury remain to be determined.